2014
DOI: 10.1159/000364834
|View full text |Cite
|
Sign up to set email alerts
|

Single-Stage Multiple-Tract Percutaneous Nephrolithotomy in the Treatment of Staghorn Stones under Total Ultrasonography Guidance

Abstract: Objective: To evaluate the safety and efficacy of single-stage multiple-tract percutaneous nephrolithotomy (PCNL) in the treatment of staghorn stones solely guided by ultrasonography (US). Patients and Methods: From May 2007 to July 2012, 55 single-stage multiple-tract PCNL procedures were performed (53 patients, of whom 2 had bilateral stones). Caliceal puncture and dilatation were performed under US guidance in all cases. The procedure was evaluated for access success, length of postoperative hospital stay, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…In our study, we achieved an 85% stone-free rate, which is comparable with other studies (84-89%) [24][25][26].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, we achieved an 85% stone-free rate, which is comparable with other studies (84-89%) [24][25][26].…”
Section: Discussionsupporting
confidence: 90%
“…Cho et al [23] found that in appropriately chosen patients, a multitract PCNL is safe and efficient. Fei et al [24] achieved a 78% stone-free rate in 55 patients with complete staghorn stones who underwent multitract PCNL. They found multitract PCNL crucial to increase total stone clearance and to reduce reliance on supplemental extracorporeal lithotripsy and/or 2nd look PCNL.…”
Section: Discussionmentioning
confidence: 99%
“…Recent publication by Wang et al [16] reports successful pultipuncture PNL in a single session by adding miniperc to the first standard access in 58 patients with comparable complication rates. Even such efforts have confirmed the feasibility of multi-access PNL under ultrasonographic guidance [17].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have demonstrated the feasibility of utilizing ultrasound as an imaging modality during PCNL, operating on mean stone burdens ranging from 2-6 cm, producing a 63 % to 100 % stone-free rate [78][79][80][81][82]. Limitations of using ultrasound as the sole technique for access include the limited use in obese patients, those with full staghorn calculi, and those lacking hydronephrosis, due to reduced visibility.…”
Section: Reducing Radiation During Percutaneous Nephrolithotomymentioning
confidence: 99%